(untitled) (Sir Salimullah Medical College Journal, 2023)
The Choledochal cyst is a rare disease of unknown etiology. Incidence of diagnosis of choledochal cyst is much higher in children (80%) than in adult (20%). It is prevalent among Asian & female populations & the incidence is 1:100000-150000. We are reporting one such case, a 57-year-old female presenting with recurrent pain with right hypochondriac region and investigations revealed type -1 choledochal cyst. This case was managed successfully by complete excision of cyst & Roux-en-Y hepatico-jejunostomy. Sir Salimullah Med Coll J 2023; 31: 120-123